1987
DOI: 10.1016/0035-9203(87)90154-4
|View full text |Cite
|
Sign up to set email alerts
|

Opisthorchis viverrini infection in rural and urban communities in northeast Thailand

Abstract: The prevalence and intensity of liver-fluke (Opisthorchis viverrini) infection were investigated among 559 patients who were born in, and had lived all their lives in, either the rural or urban northeastern Thailand. 344 (79.4%) of 433 rural dwellers were infected compared with only 69 (54.8%) of 126 urban dwellers (P less than 0.005). The intensity of infection, and the reported level of consumption of koi-pla, a favourite dish of local inhabitants prepared from uncooked freshwater fish which often contains v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Kusumaporn Chaiputcha 1,3 , Supannee Promthet 1 *, Peter Bradshaw 1 to be conducted in rural villages rather than in urban environments because rural residents are assumed to be at higher risk of infection (Songserm et al 2012b). While there is some evidence that this may be the case (Kurathong et al, 1987;Wattanayingcharoenchai et al, 2011), further studies of OV infection in urban areas are needed. The findings of the present study were expected to be useful for planning OV infection control in the urban area chosen for this study.…”
Section: Prevalence and Risk Factors For Infection By Opisthorchis Viverrini In An Urban Area Of Mahasarakham Province Northeast Thailandmentioning
confidence: 99%
“…Kusumaporn Chaiputcha 1,3 , Supannee Promthet 1 *, Peter Bradshaw 1 to be conducted in rural villages rather than in urban environments because rural residents are assumed to be at higher risk of infection (Songserm et al 2012b). While there is some evidence that this may be the case (Kurathong et al, 1987;Wattanayingcharoenchai et al, 2011), further studies of OV infection in urban areas are needed. The findings of the present study were expected to be useful for planning OV infection control in the urban area chosen for this study.…”
Section: Prevalence and Risk Factors For Infection By Opisthorchis Viverrini In An Urban Area Of Mahasarakham Province Northeast Thailandmentioning
confidence: 99%
“…It has also been shown that the prevalence and intensity of infection are greater among rural dwellers than their urban counterparts, an observation strongly associated with the habit and frequency of eating "Koi pla" [24] . This tradition …”
Section: Report Of Cases Of Opisthorchiasis By Provincementioning
confidence: 99%
“…344 (79.4%) of 433 rural dwellers were infected compared with only 69 (54.8%) of 126 urban dwellers. Infection due to O. viverrini appears to be mainly a rural problem strongly associated with the habit and frequency of eating koi-pla [24] . Tesana et al reported the prevalence of O. viverrini infection in the villages on the banks of rivers and those far from the rivers in Loei and Nong Khai Provinces, northeast Thailand.…”
Section: Thailandmentioning
confidence: 99%
“…Fish–eating ( = piscivorous) mammals, including humans, dogs and cats, act as definitive hosts, in which sexual reproduction occurs. Clonorchiasis and opisthorchiasis are prevalent in geographical regions where raw cyprinid fish ( C. sinensis and O. viverrini ) and/or shrimp ( C. sinensis ) are a staple of the diet of humans [2], [12]. Both parasites establish in the bile ducts of the liver as well as extrahepatic ducts and the gall bladder of the mammalian (definitive) host.…”
Section: Introductionmentioning
confidence: 99%